Giant gastrointestinal stromal tumor of the duodenum mimicking a pancreas head tumor: a case report - Aksoy, Erol; Üstüner, Mehmet Akif; Aydın, Osman; Bostancı, Erdal Birol (The European Research Journal, 2023)
Duodenal gastrointestinal stromal tumor (GIST) is rarely observed in the gastrointestinal system. It can be confused with pancreas pathologies as it shows an extramural growth pattern. The case is here presented of a 65-year-old male who presented with the complaints of abdominal pain, nausea and vomiting. On contrast abdominal tomography, a centrally hypodense, necrotic mass, 140×115×100 mm in size, was observed in the pancreas head. With a preliminary diagnosis of neuroendocrine tumour/serous cystic neoplasia, a Whipple + partial vena cava resection + primary repair operation was performed. The pathology was reported as duodenal GIST. The patient was discharged with medication and referred to the oncology clinic.